Description of a new Notocomplana species (Platyhelminthes: Acotylea), new combination and new records of Polycladida from the northeastern Sea of Japan, with a comparison of two different barcoding markers - Oya, Yuki; Kajihara, Hiroshi (Zootaxa, 2017)
We describe Notocomplana hagiyai sp. nov. from Ishikari Bay, Hokkaido, northern Japan. Notocomplana hagiyai sp. nov. is characterized by i) a larger prostatic vesicle relative to the seminal vesicle and ii) a Lang’s duct that is shorter than the long axis of Lang’s vesicle. Melloplana japonica (Kato, 1937) is transferred to the genus Notocomplana Faubel, 1983 based on the structure of its prostatic vesicle, and we record the finding of N. koreana (Kato, 1937) and N. septentrionalis (Kato, 1937) in western Hokkaido. A pair of new cytochrome c oxidase subunit I (COI) primers was designed to infer the phylogeny among the four species, and we concluded that COI is more informative than 16S rRNA for barcoding polyclad flatworms.